BETWEEN TASTE AND TABOO: DOG-MEAT AND THE MORAL IMAGINATION OF MIZO SOCIETY - Saidingpuii Sailo; Dr. B. Lalzarliana (IJRDO - Journal of Social Science and Humanities Research, 2026)
Food is never simply nutrition. It is a site where culture, morality and identity intersect. In Mizoram, the consumption of dog-meat illustrates this complexity. Historically valued both as food and in sacrificial rituals, dog-meat today has become one of the most contested delicacies in Mizo society. This article examines the sociological significance of dog-meat consumption through case studies of consumers and non-consumers of dog-meat in Aizawl. While some respondents describe dogs as companions too intelligent and affectionate to be eaten, others regard dog-meat as a normal if occasional, part of cultural practice, prized for its taste and status. Christianity further complicates the issue by casting dog-meat as a taboo in religious contexts, thereby reshaping cultural edibility codes. The divergent viewpoints demonstrate how food functions as a moral battlefield, where tradition, globalization and ethical sensibilities collide. By placing these narratives within the broader sociology of food, this article highlights how the contested practice of eating dog-meat mirrors deeper questions of cultural continuity, religious influence and the shifting boundaries of belonging in Mizoram.